THE MODERATING EFFECT OF DIVIDEN AND OWNERSHIP STRUCTURE ON THE RELATIONSHIP BETWEEN FREE CASH FLOW AND ENTERPRISE VALUE - Zaki Fakhroni; Indra Suyoto Kurniawan (UNEJ e-Proceeding)
The purpose of this study was to answer the phenomena occurring phenomenon both theoretically and empirically the phenomenon of potential internal conflicts of the company’s free cash flow and its use for the benefit of increasing corporate value. Such internal conflicts requires a proper solution so that no impact on the company’s failure. This study examine the role of dividends and ownership structure (majority and managerial) in moderating the relationship between free cash flow and enterprise value. The results of this study are expected to generate an alternative solution of free cash flow problems and increase corporate value. Population data in this study are companies listed on the Indonesia Stock Exchange in the period of observation in 2007-2016. The number of sample used in this study is 2.387 units of observation. Sampling techique in this study using methods of probability/random sampling. Statistical tools to test hypothesis in this study is the pure moderated regression analysis. The results showed that free cash flow has a negative and significant effect on firm value. Free cash flow could potentially cause failure of the company as a result of reduced firm value and poor financial performance. Other research results indicate that dividends and managerial ownership moderates the relationship between free cash flow and value of the company in a positive and significant. Majority ownership moderates the positive and significant to the relationship between free cash flow and enterprise value. Therefore, the mechanism of dividends and managerial ownership can be used to solve the problems of free cash flow and increase corporate value.